The Effect of Food Supplementation Program on Anthropometry, Hematology, and Parasites of Primary School Children - Christin M. Santosa, Christin M. Santosa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Food supplementation is problem solving efforts during multidimensional crisis.Objectives: This research was carried to evaluate further the advantages of the food supplementation in the primary school children towards their physical development and health status.Methods: Students with completely participation on these research and their parents agreed to informed consent were taken as inclusion criteria. The subjects of this experiment were sixth grade school children and divided into 2 groups i.e 25 control and 31 treated groups. The treatment group was given food supplementation consisting of one boiled egg and one glass of green-peas porridge (220 ml) each, three times a week for 10 weeks, whereas the control group was not given any. Observations were carried out five times: at 0, 3, 7, 10, and 13 weeks. The results were analized by the Student-t test.Results: The results showed significant increases in body weights (p0.05) between control and treatment groups neither for the boys nor girls. And until the last week faeces samples, it is never detected the situation where it is free from worm investation and protozoa infection either for control or treatment group.Conclusion: The food supplementation was apparently adequate to meet the optimal caloric and proteins requirements of these children, so that could improve physical development and health status as shown by the increased anthropometric measurements, decreasing parasite infection and steady hematological picture.Key words: food supplementation - anthropometry - hematology - parasites - primary school children